Innate lymphoid cell characterization in the rat and their correlation to gut commensal microbes. Issue 5 (13th February 2022) - Sudworth, Amanda; Segers, Filip M.; Yilmaz, Bahtiyar; Guslund, Naomi C.; Macpherson, Andrew J.; Dissen, Erik; Qiao, Shuo‐Wang; Inngjerdingen, Marit
Abstract: Innate lymphoid cells (ILCs) are important for tissue immune homeostasis, and are thoroughly characterized in mice and humans. Here, we have performed in‐depth characterization of rat ILCs. Rat ILCs were identified based on differential expression of transcription factors and lack of lineage markers. ILC3s represented the major ILC population of the small intestine, while ILC2s were infrequent but most prominent in liver and adipose tissue. Two major subsets of group 1 ILCs were defined. Lineage – T‐bet + Eomes + cells were identified as conventional NK cells, while lineage – T‐bet + Eomes – cells were identified as the probable rat counterpart of ILC1s based on their selective expression of the ILC marker CD200R. Rat ILC1s were particularly abundant in liver and intestinal tissues, and were functionally similar to NK cells. Single‐cell transcriptomics of spleen and liver cells confirmed the main division of NK cells and ILC1‐like cells, and demonstrated Granzyme A as an additional ILC1 marker. We further report differential distributions of NK cells and ILCs along the small and large intestines, and the association of certain bacterial taxa to frequencies of ILCs. In conclusion, we provide a framework for future studies of ILCs in diverse rat experimental models, and novel data on the potential interplay between commensals and intestinal ILCs. Abstract : Rat ILCs are here defined and characterized across multiple tissues, and we have defined the borders between rat NK cells and ILC1s via scRNA‐Seq. Variations of intestinal ILC frequencies in individual rats were mapped against composition of the commensal microbiota.